Masa Depan Pemanfaatan Batubara sebagai Sumber Energi di Indonesia - Pahlevi, Rinaldi; Thamrin, Suyono; Ahmad, Irdam; Nugroho, Fajar Bayu (Program Studi Magister Energi, Sekolah Pascasarjana, Universitas Diponegoro, Indonesia, 2024)
Coal is one of the potential energy sources that can be seen from the aspect of production and availability of reserves that are relatively large compared to other fossil energy sources in Indonesia. Until now, coal is still used as the basic capital for development, especially in the electricity sector. Based on the Electricity Supply Business Plan (RUPTL) 2021-2030, in terms of the achievement of the energy mix, it is still dominated by coal utilization where coal usage increased significantly from 2011 to December 2020. In the 2021-2030 RUPTL, it is explained that there are scenarios for future coal utilization with optimal and low carbon scenarios, which in both scenarios still place coal in a fairly high portion of the mix. On the other hand, the Pertamina Outlook energy also describes scenarios for future coal utilization with several scenarios, namely the Ordinary State (OS), Appropriate Sustainability (AS), and Economic Renaissance (ER) scenarios. In the OS scenario, coal will continue to experience growth, but in the US scenario, growth has decreased until the ER scenario with green economic transformation experiences a negative growth rate. In addition, coal utilization is starting to be directed towards clean coal technology as a form of effort to achieve the Net Zero Emission (NZE) target in 2060. Therefore, coal utilization must be carried out wisely by promoting the concept of clean coal technology with various strategic steps ranging from policies or regulations to the application of environmentally friendly technology as the key to success in utilizing coal that is more environmentally friendly and sustainable.